Augmented Enactive Learning:Fostering Environmental Awareness through AR Immersive Theater - Privas Breaute, Virginie (Journal of Education and Learning Environments, 2025)
In this article, we examine the potential of Augmented Reality (AR)-enhanced immersive theatre as an approach for enactive learning and as a tool for raising awareness of environmental crises. Grounded in the theories of embodied cognition and immersion, the analysis focuses on how active participation in such environments can strengthen learners’ engagement and foster a deeper understanding and retention of environmental themes. To investigate this potential, two groups of school students attended the performance: La Germination, D’autres mondes possibles (by Joris Mathieu and Nicolas Boudier, “Compagnie Haut et Court”) at “Les Ateliers – Théâtre Nouvelle Génération” (Lyon, France) in November 2023. After the performance, participants completed a post performance questionnaire designed to assess the impact of the augmented reality technology, using AR glasses on their experience and understanding. Preliminary findings based on their responses indicate that participants reported an embodied and emotional connection to environmental issues, suggesting that augmented immersive theatre can facilitate transformative learning experiences. It is argued, in this study, that this new form of theatre represents a promising environment for innovative, augmented enactive learning methodologies but that further research is needed to evaluate its long-term educational impact.